Leadless pacemaker patients following cardiac valve intervention in a long-term follow-up. (14th October 2021) - Martinez-Sande, J.L; Gonzalez, L; Garcia-Seara, J; Rodriguez-Manero, M; Fernandez-Lopez, X.A; Vega, D; Gonzalez Juanatey, J.R
Abstract: Introduction: Leadless pacemakers (LPM) have demonstrated adequate electrical performance and safety in patients with multiple commorbidities such as heart valve replacements at short-term follow-up. Purpose: We present our experience in patients with LPM and heart valve replacements at long-term follow-up. Methods: This was a prospective observational study including all consecutive LPM implantation from June 1 2005 to March 15 2021. Clinical, electrical, echocardiographic characteristics, related complications and electrical parameters were compared in 2 different groups with and with-out valve surgical procedure. Results: A total of 255 LPM were implanted. Clinical, electrical and echocardiographic characteristics are described in table 1. Mean follow-up was of 24 months. There were no significant differences in electrical performance or related complications in between both groups (Figure 1). Conclusions: Electrical performance and complications were no significantly different between both groups with and without heart valve replacements. Funding Acknowledgement: Type of funding sources: None.